2012
DOI: 10.1177/1533317512439794
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Hispanic Caregivers of Patients with Dementia

Abstract: Future studies should consider culturally tailoring interventions for Hispanic/Latino caregivers from differing subcultures, utilizing relevant technology in studies, and evaluating the functional level of the care receiver and assess where he/she is in the disease process continuum. A better understanding of within-group differences among Hispanic/Latino caregivers, especially with respect to acculturation, could lead to better tailoring of interventions. Future research should consider the possibility of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…30,31 Caregiver burden may be higher in Hispanics 15 because caregiving of adult relatives is an expectation of their culture, 32,33 because not accepting the caregiving responsibility could bring shame, 33 and because care of loved ones with dementia puts particular emphasis on family centered care, 34,35 consistent with the concept of familism often identified with Hispanic caregivers. 36-38 While most caregivers report no guilt after nursing home placement of persons with dementia, 7 this is less common in Hispanics, 7,39 who delegate less care.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…30,31 Caregiver burden may be higher in Hispanics 15 because caregiving of adult relatives is an expectation of their culture, 32,33 because not accepting the caregiving responsibility could bring shame, 33 and because care of loved ones with dementia puts particular emphasis on family centered care, 34,35 consistent with the concept of familism often identified with Hispanic caregivers. 36-38 While most caregivers report no guilt after nursing home placement of persons with dementia, 7 this is less common in Hispanics, 7,39 who delegate less care.…”
Section: Discussionmentioning
confidence: 96%
“…7 The burden of caregiving for a person with dementia may be higher in Hispanics compared to Non-Hispanic Whites. 15 There is a paucity of research in the characteristics of urban Hispanic caregivers in New York City, who have a high burden of psychosocial and medical stressors 16 that may compound the burden of caregiving. Thus, we recruited 139 Hispanic dementia caregivers for a clinical trial comparing counseling interventions, including a family based intervention, 17 and collected detailed data in-person on their demographics and mental health including caregiver burden and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Few intervention studies have been conducted with Hispanic caregivers of older adults with dementia (Llanque & Enriquez, 2012), even though previous research has shown that Hispanic caregivers could greatly benefit from receiving training in caregiving activities, information about services for caregivers and patients, and Spanish-language, culturally sensitive materials (NAC and Evercare, 2008). The creation of Cuidate Cuidador contributed to the field by offering a new, consumer-friendly, bilingual and technologically appealing vehicle for Hispanic caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that caregivers who participate in a support group report a number of health and social benefits, including reduced depression and feelings of isolation; improved understanding of ADRD and its management; and less fatigue (Biegel, Sales, & Schulz, 1991; Llanque & Enriquez, 2012; Pearlin, Aneshensel, Mullan, & Whitlach, 1997). However, reaching these support groups can be difficult for many caregivers due to distance and their caregiving obligations (Karlawish et al, 2011; Reynoso-Vallejo, Henderson, & Levkoff, 1998).…”
mentioning
confidence: 99%
“…In a review of interventions for Latino CGs, Llanque and Enriquez 30 concluded that numerous approaches were helpful in decreasing depressive symptoms and improving CGs’ quality of life, including: supportive therapy, family therapy, coping strategy training and psycho-education, which can be delivered in person, via telephone communication or using technology-based interventions) 31,32 . A low-cost, easily obtainable intervention such as a FN devoted to CG stress management could be potentially helpful to this group.…”
mentioning
confidence: 99%